HUBUNGAN POLA ASUH OTORITER DENGAN SELF ESTEEM SISWA MTSS AL. ITTIHADIYAH T.A 2022/2023 - Annisa Fitri Chairani; Widya Utami Lubis (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the relationship between authoritarian parenting and students' self-esteem at MTSS Al. Ittihadiyah. The hypothesis proposed is that there is a positive and significant relationship between authoritarian parenting and self-esteem at MTSS Al.Ittihadiyah. The research method used is descriptive quantitative approach with the type of research used is descriptive correlational research. Determination of the sample of this study is a population study of 86. The sample in this study was 40 people to obtain the necessary data, so in this study the researchers used data collection tools in the form of questionnaires and documentation. Furthermore, the results of research in MTSS Al. Ittihahadiyah uses the calculation of peroduc moment correlation. The two variables are authoritarian parenting (X) and self-esteem (Y). The level of student authoritarian parenting is 69.12% in the high category, the level of self-esteem is 64.12% in the high category, the level of the relationship between authoritarian parenting and self-esteem is 0.312> 0.226. This shows that there is a relationship between authoritarian parenting and self-esteem in students. Based on the discussion and data analysis, it can be concluded that the hypothesis which states "there is a positive and significant relationship between authoritarian parenting and self-esteem in MTSS Al.Ittihahadiyah" can be accepted. Where, the higher the authoritarian parenting, the higher the student's self-esteem.